SRT451 - Outdoor Recreational Skills and Management / Faculty of Sports Science & Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2021)
This course is designed to develop knowledge, skill and interest on the outdoor recreation that will lead to lifelong physical exercise within the appreciation of the surrounding environment for both educational and recreational purpose. Students will learn activities include camping, orienteering, first aid, survival, abseiling, kayaking and rope course.